Analisis Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha Pada Pemuda di Kecamatan Salem - Fadli Ahmad Hamzah; Hendri Sucipto; Dwi Harini (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to test and prove the existence of a partial and simultaneous influence between internal factors, external factors and emotional factors on the interest in youth entrepreneurship in Salem District. This type of research is quantitative research using associative research methods. The sampling technique in this study used propotional random sampling using the Slovin formula. Data collection was carried out by distributing questionnaires to 100 respondents who were youths of Salem District. The analytical methods used in this study consist of validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests.